“A So-Called Tenants’ Union”: Defining the Organizational Power of Tenants within and outside the Law - Shafei, Seema (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2022)
How is a tenants’ union defined within the parameters of the law? How have tenants been defining themselves as a union outside of the law? This paper will examine the answers to these questions by laying out the historical context of the current rental regime in Ontario, analyzing the current case law on tenant associational activity, and highlighting the organizational tactics that tenants’ associations have used to build power where the law has failed to protect their interests. While advancing a legal case for robust tenant associational rights may force landlords to the bargaining table, the future of tenants’ associations in and outside of the law should draw on lessons learned from the labour movement in Canada with a “whole-worker organizing” approach in mind.